Pembinaan Life Skill Entrepreneurship Remaja Melalui Pemanfaatan Barang Bekas Menjadi Gantungan Kunci dan Dompet - Slamet Arofik; Abdul Jalil Jawhari (LP3M STAI Darussalam Krempyang Nganjuk, 2019)
The Community Service Program (PkM) has the theme “Skills Improvement Assistance by” and takes the location of mentoring by the youth community (Dibaiyah and IPPNU members) Kedungrwant Hamlet, Drenges Village, Kertosono District, Nganjuk Regency. The target of service is focused on improving the skills of the younger generation towards the use of used goods to be useful and even valuable. This effort is based on the observation that there is a lot of potential that can be developed considering that the available assets are also very abundant. However, so far there are still obstacles and it has not been maximal in preaching. The type of research used is qualitative research with ABCD (asset based community development) approach. Data collection was carried out in the Kedungringin youth community from among young women members of Jamiyah, Dibaiyyah and local IPPNU members by conducting in-depth interviews with informants, observations, documentation and recording studies. The results of the analysis state that the potential and skills of youth can be encouraged and optimized so that with this program, it is not only keeping the environment clean from piles of useless used goods into useful goods and has a high selling value. .